2017
DOI: 10.25135/acg.oc.28.17.06.029
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of a singly bridged biscalix[6]arene and evaluation of its alkali metal recognition properties

Abstract: This article describes one-step synthesis of a singly bridged biscalix[6]arene (2) and evaluation of its recognition properties towards alkali metal ions for the first time. Synthesis of 2 was accomplished through coupling of two 4-tert-butylcalix[6]arene units with one molecule of diethyleneglycol ditosylate. Both base and linker were found to play a role in the outcome of coupling reaction for the simple and efficient synthesis of 2. Complexation ability of 2 was studied by liquid-liquid extraction using alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Piqued by the previous work 10 , KHCO 3 -diethyleneglycol ditosylate combination have been further explored in this report to afford singly-bridged biscalixarenes. Thus, the substrates calix [6]arene (1b), calix [4]arene (1c) and p-tert-butylcalix [4]arene (1d) were reacted with KHCO 3 and diethyleneglycol ditosylate as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Piqued by the previous work 10 , KHCO 3 -diethyleneglycol ditosylate combination have been further explored in this report to afford singly-bridged biscalixarenes. Thus, the substrates calix [6]arene (1b), calix [4]arene (1c) and p-tert-butylcalix [4]arene (1d) were reacted with KHCO 3 and diethyleneglycol ditosylate as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 91%
“…During the previous work on synthesis of biscalix [6]arene 2 from 1a, it was observed that changing the linker to triethyleneglycol ditosylate led to formation of calix[6]crown 3 10 . This part of the study was conducted to further investigate the effect of linker over the outcome of this KHCO 3 mediated reaction of bifunctional linkers with 1a (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since past two decades, I have been involved in exploiting calixarene based hosts for various targets like cesium 13,14 and fullerenes [15][16][17] , and developing synthetic protocols for selective functionalization of calixarenes 18,19 .…”
Section: Introductionmentioning
confidence: 99%